PARENTAL PERSPECTIVES ON PHYSICAL ACTIVITY IN PRESCHOOL: READINESS FOR PARTICIPATION AND BARRIERS TO INVOLVEMENT - Grujić, Gabrijela; Lapčević, Gorana; Prazina, Vanja (Metodička teorija i praksa, 2026)
This study examined parents’ attitudes toward the importance of physical activity in preschool, their readiness to participate in physical education activities, perceived barriers to involvement, and preferred forms of cooperation with preschool teachers. The study was conducted on a sample of 50 parents whose children attend the “Čukarica” Preschool in Belgrade, using a structured questionnaire. Data were analyzed using descriptive statistics and independent-samples t-tests. The results showed that parents expressed strongly positive attitudes toward the role of physical activity in children’s health, motor development, and psychosocial well-being. However, their actual participation was conditioned by personal opportunities, motivation, educational level, and organizational conditions within the preschool. The most frequently reported barriers were lack of time, unsuitable activity schedules, and feelings of insecurity, while the most encouraging forms of cooperation were short, well-organized, and enjoyable activities, such as family sports days, movement workshops, and eco-walks. Activities led by preschool teachers were rated more favorably than those involving external sports specialists. The findings indicate the need to develop diverse, accessible, and flexible models of cooperation that strengthen family-preschool partnership and promote greater parental involvement in preschool physical education.
Keywords: physical education; questionnaire; parental involvement; preschool teacher